Stanovsko gledališče v Ljubljani v sezoni 1838/39 - Smolej, Tone (Jezik in slovstvo, 2024)
This paper analyses the 1838/39 season of the German Theatre of the Carniolan Provincial Estates (Ständisches Theater) in Ljubljana, focusing on its artistic output. The introductory section describes the archival material on the basis of which the theatre’s repertoire was reconstructed and then discusses the role of the theatre’s impresario, Ferdinand Funk, and the most important plays which were perfor-med there. In addition to the works of the Austrian playwrights Ferdinand Raimund, Johann Nestroy, Carl Meisl, and Friederich Halm, those of Eugene Scribe and Shakespeare in German translation fe-atured prominently; women playwrights were also noticeably represented in the theatre’s repertoire. Before the 1848 revolutions the Slovene intelligentsia also patronised the Theatre of the Carniolan rovincial Estates, which was the only theatre in Ljubljana at the time, and refined their taste for dramatic art there.
Keywords: 1838/39 theatre season; Funk, Ferdinand; gledališka sezona 1838/39; Halm, Friedrich; Stanovsko gledališče v Ljubljani; Theatre of the Carniolan Provincial Estates